The effects of monosaccharides on the physico-electrochemical properties of chitosan based solid polymer electrolytes (SPEs) - Nurul Iffah Ismail; Saiyidah Nafisah Saidin; Nur Hani Ra’il; Azizan Ahmad; Nadhratun Naiim Mobarak (Penerbit Universiti Kebangsaan Malaysia, 2022)
Monosaccharides have shown their potential as plasticizers in solid polymer electrolytes (SPEs) due to the presence of numerous hydroxyl (OH) functioning groups. Glucose and fructose were used in this study. The effect of monosaccharides on physico-electrochemical properties of solid polymer electrolytes based on chitosan have been studied. Chitosan-based polymer electrolytes have been successfully plasticized using a solution-casting technique at six different weight percentages (0-30 wt.%). The result shows that 15 wt.% was the highest ionic conductivity achieved by both chitosan-glucose (CG) and chitosan-fructose (CF) systems. Lithium transference number (TLi +) analysis showed that CF had a high number of lithium ions compared to the CG system, with values of 0.26 and 0.14, respectively. In addition, Linear Sweep Voltammetry (LSV) analysis shows that the electrochemical stability for the CG system was 2.98 V compared to 3.20 V for the CF system. This discovery demonstrates that monosaccharides have the potential to be used as plasticizers due to the presence of several oxygen atoms in the structure, which act as a coordination site for cation interaction and can also improve the ion mobility and ionic conductivity of chitosan-based solid polymer electrolytes.